Effect of carbon fiber on the properties of polymer cement based building sealant. Issue 46 (21st September 2022) - Wang, Zhihang; Bai, Erlei; Ren, Biao; Huang, He; Ren, Weibo
Abstract: The working property, bond property, and mechanical property of five kinds of polymer cement based building sealant (PCBS) with different carbon fiber content were tested. The effect of carbon fiber on the properties of PCBS was discussed by analyzing the variation of the leveling performance, consistency, low temperature flexibility, surface dry time, elastic recovery rate, tensile mechanical property, and shear mechanical property of PCBS with carbon fiber content. And the modification mechanism of carbon fiber on PCBS was interpreted using scanning electron microscopy and mercury intrusion porosimetry techniques. The results shows that PCBS still has good working property and bonding property with carbon fiber addition. As the carbon fiber content increases, the leveling performance and low temperature flexibility of PCBS are unaltered., the consistency increases, while the surface drying time and elastic recovery rate decrease. The tensile and shear mechanical properties of PCBS can be improved by adding carbon fiber. With the increase of carbon fiber content, the strength performance indexes of PCBS increase, while the energy consumption performance indexes first increased followed by a decrease. When the carbon fiber content is 0.1%, the properties of PCBS is the best. The pore structure of PCBS gradually deteriorates, and the total porosity and the percentage of macropores increase with carbon fiber addition. Carbon fiber primarily exerts cracking resistance and internal deterioration effects in PCBS. Abstract :